Quality Control of Sunscreen Products: A Validated HPLC Method for the Analysis of Avobenzone and Oxybenzone - Novy Inti Fauziah; Aqnes Budiarti; Khoirul Anwar (Natural Sciences Engineering and Technology Journal, 2025)
Avobenzone and oxybenzone are commonly used ultraviolet (UV) filters in sunscreen products, offering broad-spectrum protection against harmful solar radiation. Accurate determination of these compounds in sunscreen formulations is crucial for quality control and ensuring consumer safety. This study aimed to develop and validate a high-performance liquid chromatography (HPLC) method for the simultaneous determination of avobenzone and oxybenzone in commercial sunscreens. The HPLC method utilized a C₁₈ column with a mobile phase of methanol:aquabidest (93:7, v/v) at a flow rate of 1.0 mL/min and a detection wavelength of 320 nm. The method was validated for linearity, sensitivity, selectivity, precision, and accuracy. The validated method was then applied to quantify avobenzone and oxybenzone in three different brands of commercial sunscreen products. The developed HPLC method demonstrated excellent linearity for both avobenzone (r = 0.9998) and oxybenzone (r = 0.9995). The method was also highly sensitive with low limits of detection (LOD) and quantitation (LOQ) for avobenzone (0.13 μg/mL and 0.43 μg/mL, respectively) and oxybenzone (0.35 μg/mL and 1.15 μg/mL, respectively). The method exhibited good selectivity and precision (%RSD ≤ 2%). Accuracy, as determined by recovery experiments, was within the acceptable range (100.01%-100.77% for avobenzone and 99.66%-100.81% for oxybenzone). The levels of avobenzone and oxybenzone in the analyzed sunscreen brands (A, B, and C) were found to be within the regulatory limits. In conclusion, the validated HPLC method provides a reliable and efficient means for the simultaneous quantification of avobenzone and oxybenzone in sunscreen products, contributing to the quality control and safety of these widely used formulations.